STRATEGI PENCITRAAN PARTAI DEMOKRAT WILAYAH KOTA BANJARMASIN SAAT PEMILU TAHUN 2019 - Fahrianoor Fahrianoor (Metacommunication: Journal of Communication Studies, 2020)
The Democratic Party in the 2004 General Elections entered the top five political parties with the highest electability in Indonesia. This party's victory was not only achieved at the central level but also the regional level. The party's positive trend continued into the 2009 elections. The Democratic Party experienced a significant decline in votes in 2014 due to the issue of corruption. The decline in votes has certainly had an impact on the preparation of the Democratic Party in the 2019 elections. The Democratic Party must prepare an appropriate political winning strategy, both at the central and regional levels. This study aims to determine the Democratic Party's imaging strategy in the city of Banjarmasin. This research uses a qualitative method, with a qualitative descriptive approach. The theory used in this study is the theory of empathy. The results showed that there were three imaging strategies carried out by the Democratic Party, namely imaging through the management of issues, through consulting services, and mass media. This imaging strategy is managed for the 2019 elections. This research generates suggestions that the Democratic Party should utilize issues that can improve the party's image. The Democratic Party should also use the services of political consultants from professional circles to boost the party's positive image. The use of mass media should also not be limited to party leaders, but the level of functionaries.